Oral health treatment needs in people with substance use disorders: Study cross-sectional - Syakhshiyyah, Azka As; Lestari, Sri; Theresia, Tiarma Talenta; Louisa, Marie; Putri, Anzany Tania Dwi (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Drug abuse is widespread in society and has led to dependency and death. Substance use disorders can lead to various health problems, particularly increasing susceptibility to various dental and oral diseases such as caries, tooth loss, and periodontal disease. This study aimed to desribe the dental and oral treatment needs of individuals with substance use disorders at Lido National Rehabilitation Center of Narcotics, Bogor Regency. Methods: This study employed a descriptive observational design with a cross-sectional approach and a sample size of 101 respondents. Data were collected using Decay Score to measure the need for restorative treatment, the Missing Score to evaluate the need for prosthetic treatment, and the CPITN index to assess periodontal conditions. Data analyzed using univariate analysis. Results: A total of 766 (80%) teeth had caries requiring restorative treatment and 152 (16%) teeth were missing and required prosthetic replacement. The CPITN examination revealed that 92 (91%) respondents required treatment (TN) with category TN 2 in the form of scaling, root planing, and oral hygiene instructions. Conclusions: Most individuals with substance use disorders require restorative treatment, prosthetic, and periodontal treatment.KEY WORDS: Substance use disorders, treatment needs (TN), CPITNKebutuhan perawatan gigi dan mulut pada penyalahguna narkoba: Studi cross-sectionalABSTRAKPendahuluan: Narkoba saat ini banyak disalahgunakan oleh masyarakat luas hingga menimbulkan ketergantungan dan kematian. Penyalahgunaan narkoba dapat menyebabkan berbagai masalah kesehatan, terutama rentan terhadap berbagai penyakit gigi dan mulut seperti karies, kehilangan gigi, dan penyakit periodontal. Penelitian ini bertujuan untuk mengetahui kebutuhan perawatan gigi dan mulut pada penyalahguna narkoba di balai besar rehabilitasi badan narkotika nasional Lido Kabupaten Bogor. Metode: Penelitian observasional deskriptif dengan rancangan penelitian cross-sectional dan jumlah sampel sebanyak 101 responden. Pengumpulan data menggunakan skor Decay untuk mengukur kebutuhan perawatan restorasi, skor Missing untuk mengukur kebutuhan perawatan protesa, dan indeks CPITN. Analisis data dilakukan menggunakan analisis univariat. Hasil: sebanyak 766 (80,46%) gigi mengalami karies dan membutuhkan perawatan restorasi serta sebanyak 152 (15,97%) gigi yang hilang serta membutuhkan pembuatan protesa. Hasil pemeriksaan CPITN, sebanyak 92 (91%) responden membutuhkan perawatan (TN) dengan kategori TN 2 berupa perawatan scaling, root planing, dan instruksi untuk peningkatan oral hygiene. Simpulan: Sebagian besar pasien penyalahguna narkoba membutuhkan perawatan restorasi, protesa, dan perawatan penyakit periodontal.KATA KUNCI: Penyalahguna narkoba, kebutuhan perawatan (TN), CPITN